Developing a national patient safety plan in Guatemala - Randall Lou-Meda; Sindy Méndez; Erwin Calgua; Mónica Orozco; Bria J. Hall; Natalie Fahsen; Brad M. Taicher; Joseph P. Doty; Julio García Colindres; Carlos Soto Menegazzo; Henry E. Rice (Pan American Health Organization, 2019)
Objective. Patient safety is challenging for health systems around the world, particularly in low- and middleincome countries such as Guatemala. The goal of this report is to summarize a strategic planning process for a national patient safety plan in Guatemala. Methods. This strategic planning process involved multiple stakeholders, including representatives of the Guatemala Ministry of Health and Social Assistance, medical leadership from across the public health system, and academic experts from Guatemala and the United States of America. We used mixed methods (quantitative and qualitative surveys) and a nominal group technique at a national symposium to prioritize patient safety challenges across Guatemala, and subsequent meetings to develop a national patient safety plan. Results. This national patient safety plan outlines four domains to advance patient safety across the public hospital system over a five-year period in Guatemala: leadership and governance, training and awareness, safety culture, and outcome metrics. For each domain, we developed a set of goals, activities, outputs, and benchmarks to be overseen by the Ministry of Health. Conclusions. With this national patient safety plan, Guatemala has made a long-term commitment to improving patient safety across the public hospital system of Guatemala. Future efforts will require its extension to all levels of the Guatemalan health system.